2020
DOI: 10.1111/1365-2656.13174
|View full text |Cite
|
Sign up to set email alerts
|

Holocene extinctions of a top predator—Effects of time, habitat area and habitat subdivision

Abstract: 1. Loss of habitat and changes in the spatial configuration of habitats are major drivers of species extinctions, but the responses to these drivers differ between organisms. To advance theory on how extinction risk from different types of habitat alteration relates to species-specific traits, there is a need for studies of the long-term extinction dynamic of individual species.2. The goal of this study was to quantify how habitat area and the spatial configuration of habitats affect extinction rate of an aqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…(2007) showed that for a butterfly species, the total amount of suitable habitat was the best predictor of the probability of metapopulation persistence when compared to the number of patches, the average patch area, and the habitat connectivity. Similarly, Englund et al., (2020) observed that metapopulation size (cumulated area of connected lakes) has been a good predictor of the rate of pike metapopulation extinctions since the end of the Pleistocene. Our study is in line with those observations by showing that the model with metapopulation size (area * Occ, M6) is among the best models and is slightly outcompeted (∆AIC = −0.21) by the very similar one (M7) in which both area and occupancy are entered as predictors.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…(2007) showed that for a butterfly species, the total amount of suitable habitat was the best predictor of the probability of metapopulation persistence when compared to the number of patches, the average patch area, and the habitat connectivity. Similarly, Englund et al., (2020) observed that metapopulation size (cumulated area of connected lakes) has been a good predictor of the rate of pike metapopulation extinctions since the end of the Pleistocene. Our study is in line with those observations by showing that the model with metapopulation size (area * Occ, M6) is among the best models and is slightly outcompeted (∆AIC = −0.21) by the very similar one (M7) in which both area and occupancy are entered as predictors.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, Englund et al, (2020) observed that metapopulation size (cumulated area of connected lakes) has been a good predictor of the rate of pike metapopulation extinctions since the end of the Pleistocene. Our study is in line with those observations by showing that the model with metapopulation size (area * Occ, M6) is among the best models and is slightly outcompeted (∆AIC = −0.21) by the very similar one (M7) in which both area and occupancy are entered as predictors.…”
Section: Importance Of Metapopulation Dynamicsmentioning
confidence: 81%
“…Pike in the Baltic Sea, and elsewhere, may migrate to the spawning sites from surrounding areas (Karås and Lehtonen, 1993;Bosworth and Farrell, 2006) so abundance and size may be related to the connectivity between the studied bays and other suitable areas (Englund et al, 2020). Surrounding habitat was not assessed here and in this study we can therefore not infer anything about the importance of surrounding habitat quality or connectivity between habitats.…”
Section: Discussionmentioning
confidence: 92%
“…3, Supporting information). Late Pleistocene Eurasian large mammals had their best survival conditions when several well‐connected habitat patches were available, which allowed maintenance of healthy metapopulation structures (Hanski and Mononen 2011, Englund et al 2020). For now‐extinct species, the degree of connection among patches started to deteriorate noticeably during the 46–36 ka interval (Fig.…”
Section: Discussionmentioning
confidence: 99%